Configuring ISA 2000 server: building firewalls for Windows 2000 (Rockland, MA : Syngress, 2001)
Microsoft's flagship ISA Server delivers the Internet to your customers! As the demand for Internet connectivity reaches a fever pitch, system administrators are being challenged to connect more and more systems to the Internet without compromising security or network performance. ISA Server 2000 provides system administrators with a revolutionary management infrastructure that addresses the two greatest needs of Enterprise-wide Internet connectivity: Security and speed. Written by best-selling author of several MCSE 2000 study guides, this book will provide the system administrators with an in depth understanding of all the critiacl features of Microsoft's flag ship Internet Server. Configuring ISA Server 2000 shows network administrators how to connect a network to the Internet, maintain the connection, and troubleshoot remote users' hardware and software configuration problems. * Up-to-date coverage of new products specific to Windows 2000 * Shows network administrators how to supply e-mail whilst maintaining network security * Focuses on providing secure remote access to a network.
Introduction to Microsoft ISA Server -- ISA Server in the Enterprise -- Security Concepts and Security Policies -- ISA Server Deployment Planning and Design -- ISA Server Installation -- Managing ISA Server -- ISA Architecture and Client Configuration -- Configuring ISA Server for Outbound Access -- Configuring ISA Server for Inbound Access -- Publishing Services to the Internet.
Includes index.
Keywords: Microsoft ISA server; Client/server computing; Microsoft ISA server; Electronic books